Stress Analysis of Four Kinds of Flexible T- typed Coupling Joint - Ren Ning; Wang Zhongying; Zhou Feng (Jixie chuandong)
The corner- filleted flexural hinge,the elliptical- rectangle flexural hinge,the parabola- rectangle flexural hinge and the hyperbolic- rectangle flexural hinge are used in the structure of the flexible T-typed coupling joint. In order to explore their load- bearing,the finite element model is set up based on the solid element SOLID92,and the corresponding boundary conditions are used. The results showed that,the load- bearing of the flexible T- typed coupling joint that made of the elliptical- rectangle flexural hinge is the strongest; the maximum bending stress,torsion stress and tensile stress is mainly depends on the minimum thickness,and all the stress decreases with the increase of the width and the minimum thickness,which keep the same with the results of the influence of the structural parameters of the elliptical- rectangle flexural hinge on its maximum bending stress,maximum torsion stress and the maximum tensile stress.